Finite element analysis of crushing of thin-walled structures - Tan, Genever Bee Lu. (2011)
In today’s context, thin-walled structures are widely used in many applications. These thin-walled structures usually fail due to the buckling of the shell. As such, it is of the utmost importance for these structures to be strong enough and able to perform its intended function with a relatively reasonable reliability. Hence, to improve the thin-walled structure’s capability to withstand a greater loading force, a compliant core was adopted.